Quasi atomic layer etching of SiO2 using plasma fluorination for surface cleaning - Koh, Kyongbeom; Kim, Yongjae; Kim, Chang Koo; Chae, Heeyeop (Journal of Vacuum Science and Technology A: Vacuum, Surfaces and Films, 2018)
In this work, quasi atomic layer etching process using surface fluorination was investigated for native oxide (SiO2) cleaning with CHF3, O2, and Ar in inductively coupled plasmas. SiO2 surface was fluorinated by fluorocarbon radicals generated from CHF3 plasma in the first step. In the following step, the fluorinated SiO2 was removed by O2 or Ar plasma. O2 plasma was used to minimize carbon contamination caused by fluorocarbon layer, and Ar plasma was used to prevent the risk of surface reoxidation by O2 plasma. The effects of various process variables were investigated such as radio frequency source power, bias power, and processing time of each step. As the exposure time of fluorination step increased, the etch rate increased gradually and saturated. As the exposure time of O2 plasma processing time increases, SiO2 removal rate was also saturated and self-limited characteristic was confirmed. For surface cleaning, the authors achieved the atomic layer removal rates of 6.8 Å/cycle with the controlled small source power of 25 W and with the bias power of 5 W. When Ar plasma was applied instead of O2 plasma for the SiO2 removal, the similar self-limited etch rate was achieved and the etch rate was 4.0 Å/cycle. The self-limited atomic layer etching process makes discrete removal rate control possible.
Keywords: Atomic layer etching; Carbon contamination; Fluorocarbon layers; Fluorocarbon radicals; Plasma fluorination; Plasma processing time; Radio frequency source power; Surface fluorination